Special Issue – Social responsibility and continuity in family firms - Dieguez-Soto, Julio; Callejón-Gil, Ángela (European Journal of Family Business, 2019)
Special Issue – Social Responsibility and Continuity in Family Firms Guest Editors: Julio Diéguez Soto and Ángela Callejón-Gil